2020
DOI: 10.1002/ctm2.241
|View full text |Cite
|
Sign up to set email alerts
|

MAFG‐AS1 promotes tumor progression via regulation of the HuR/PTBP1 axis in bladder urothelial carcinoma

Abstract: Our findings indicate that MAFG-AS1 acts as an oncogene to promote the progression of BUC via regulation of the HUR/PTBP1 axis. Targeting MAFG-AS1 may provide a novel strategy for individualized therapy and a potential biomarker for prognosis of BUC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…Besides, Xiao et al showed that MAFG-AS1 can promote BC proliferation, invasion, metastasis, and EMT in vitro and in vivo. Mechanistically, MAFG-AS1 directly binding to Hu antigen R (HuR) could recruit ubiquitin-specific proteinase 5 (USP5) to prevent HuR from degrading by ubiquitination [ 34 ]. For six remaining FRlncRNAs (AL136084.3, AC062017.1, AC008074.2, AC018653.3, LINC01767, and AC132807.2), there were no studies to report their prognostic roles in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Xiao et al showed that MAFG-AS1 can promote BC proliferation, invasion, metastasis, and EMT in vitro and in vivo. Mechanistically, MAFG-AS1 directly binding to Hu antigen R (HuR) could recruit ubiquitin-specific proteinase 5 (USP5) to prevent HuR from degrading by ubiquitination [ 34 ]. For six remaining FRlncRNAs (AL136084.3, AC062017.1, AC008074.2, AC018653.3, LINC01767, and AC132807.2), there were no studies to report their prognostic roles in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Herrera-Solorio et al (2020) showed that lncRNA SOX2-OT modulates an orchestrated resistance mechanism, promoting poor prognosis and human lung malignancy through genetic, epigenetic, and posttranslational mechanisms. Xiao et al (2020) found that the lncRNA MAFG-AS1, which is highly expressed in bladder urothelial carcinoma, is correlated with aggressive characteristics and poor prognosis of bladder urothelial carcinoma. As for BRCA, IRNAS HOTAIR, SPRY4-IT1, GAS5, MATAR25, PANDAR, and MATAR25, new players in tumor development and prognosis, have shown owning potential clinical applications in BRCA (Soudyab et al, 2016;Nagini, 2017;Chang et al, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Recent developments in next-generation sequencing technologies have greatly expanded our knowledge of non-coding RNAs, and these non-coding RNAs are considerably more abundant than mRNAs (26). Many studies have revealed the role of lncRNAs in cancer development, indicating their potential as novel biomarkers for cancer diagnosis and prognosis (27)(28)(29). To better understand the molecular markers of relapsed HCC, we comprehensively analyzed the database and identified lncRNAs that can be used to predict OS and RFS.…”
Section: Discussionmentioning
confidence: 99%